Perbandingan 3 Metode Data Mining Untuk Penentuan Hipertensi Di Rumah Sakit Umum Daerah Dr. Moewardi Surakarta - usman, taufiq; Umi Fadilillah, S.T M.Eng (2016)
changes of lifestyle and many foods containing fat high as well as drinks containing alcohol that consumed by the community could cause the occurrence of hypertension, it can happen because the community doesn't know factor of hypertension. This data patients in RSUD Dr. Moewardi Surakarta who previously only will be left alone and only causing accumulation of big data, this could be useful information to determine the hypertension. This research aims to the determination of hypertension based on factor the most affect using in data mining techniques with using three method are Decision tree Algoritma ID3, naïve bayes and regresi linier. While attribute - an attribute that used is gender, age categories, intake fat, consumption of alcohol and the results of hypertension. The results of a comparison this method using Software Rapidminer 5 and Microsoft Excel to know a method of the most accurate, so from the implementation of three method it can be seen based on virtue of value accuracy, precision, recall. Method of linear regression it is better used with having value accuracy 72,09% and precision 78,52% . An atribute that most affect in the determination of hypertension in RSUD Dr. Moewardi Surakarta is the consumption of alcohol.